THE EFFECT OF BUDGET PARTICIPATION, TOTAL QUALITY MANAGEMENT, AND ENVIRONMENTAL UNCERTAINTY ON MANAGERIAL PERFORMANCE KI IN PT. TONASA LINES SHIPPING IN PANKEP DISTRICT - Muh. Zulfadli; Hajering Hajering; Amiruddin Amiruddin (Universitas Muhammadiyah Makassar, 2021)
In this study the author has the objective to determine the effect of budget participation, total quality management and environmental uncertainty on managerial performance on PT Pelayaran Tonasa Lines in Pangkep Regency. The hypothesis of this study is: Suspected of budget participation, total quality management and environmental uncertainty have a significant impact on the performance of managerial on PT Pelayaran Tonasa Lines in Pangkep Regency. The data required in this study is primary data in the form of respondents’ assessment of participation, total quality management, environmental uncertainty and performance of managerial. Data collection methods used in this study is the questionnaire as well as a literature review on the books related to the subject matter covered. Data analysis techniques used by Multiple Linear Regression Test, t test, F test, Coefficient of Determination Test. The results of this study indicate: (1) budget participation a positively and significantly effect on the managerial performance; (2) total quality management a positively and not significantly effect on the managerial performance; and (3) environmental uncertainty a positively and significantly effect on the managerial performance